Removal of Heavy Metals from Contaminated Soil by Washing CaCI2 and Effect of pH - Anwar Ahmad; Khairul Nizar Ismail, Dr.; Ragunathan Santiagoo; Rumana Ghufran (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.